The Effect of Probiotics on Bacillus sp Population, Water Quality, and Growth Rate of Striped Catfish (Pangasianodon hypophthalmus) in Pounds without Water Change - Yuke Eliyani; Azam Bachur Zaidy; Tatty Yuniarti (Jurnal Perikanan dan Kelautan, 2022)
This study aims to determine the effect of adding probiotics to water quality, Bacillus sp population and production performance of striped catfish. Completely randomized design experiment with three treatments ponds without probiotics without changing water (NN), ponds plus probiotics without changing water (PNW) and ponds given probiotics with 10% water change per day (PW). three replications each. The results showed that the water quality in the experimental pond was still within the acceptable range for fish growth. The TOM levels of the ponds that were given probiotics were lower than the control ponds. The PNW ponds with the lowest TOM levels turned out to have the highest TAN levels. The population of Bacillus sp in NN, PNW and PW ponds was not significantly different (P>0.05), however, the population of Bacillus PNW was 42.51% higher than NN, while PW was 17.38% higher than NN ponds. The abundance of plankton and the uniformity index of NN, PNW, and PW ponds were not significantly different (P>0.05). The abundance of plankton in NN was 203% higher than PNW and PW was 73% higher than PNW ponds. The growth rate and individual weight gain were significantly different (P<0.05), the growth rate of the PNW pond was higher than that of the NN pond, while the PW pond was the same as the PNW and NN ponds. The highest additional individual weight was in the PW pond, followed by the PNW pond and the lowest in the NN pond. Survival and biomass addition were not significantly different (P>0.05).